Development of a Novel Fluorescence Assay Based on the Use of the Thrombin-Binding Aptamer for the Detection of O6-Alkylguanine-DNA Alkyltransferase Activity - Maria Tintoré; Anna Aviñó; Federico M. Ruiz; Ramón Eritja; Carme Fàbrega (Journal of Nucleic Acids)
Human O6-alkylguanine-DNA alkyltransferase (hAGT) is a DNA repair protein that reverses the effects of alkylating agents by removing DNA adducts from the O6 position of guanine. Here, we developed a real-time fluorescence hAGT activity assay that is based on the detection of conformational changes of the thrombin-binding aptamer (TBA). The quadruplex structure of TBA is disrupted when a central guanine is replaced by an O6-methyl-guanine. The sequence also contains a fluorophore (fluorescein) and a quencher (dabsyl) attached to the opposite ends. In the unfolded structure, the fluorophore and the quencher are separated. When hAGT removes the methyl group from the central guanine of TBA, it folds back immediately into its quadruplex structure. Consequently, the fluorophore and the quencher come into close proximity, thereby resulting in decreased fluorescence intensity. Here, we developed a new method to quantify the hAGT without using radioactivity. This new fluorescence resonance energy transfer assay has been designed to detect the conformational change of TBA that is induced by the removal of the O6-methyl group.